Walk test: Ventilatory and cardiovascular responses and their relationship with the walking distance covered by patients with tuberculosis sequelae - Betancourt-Peña, Jhonatan; Molano-Murillo, Juan; Lopez, Ingrid Lorena; Ávila-Valencia, Juan (Universidad y Salud, 2023)
<span class="NormalTextRun SCXW105320746 BCX0" data-ccp-parastyle="Resumen" data-ccp-parastyle-defn="{"ObjectId":"986dfd32-bcdb-4f5c-a256-cb7ea477bee7|75","ClassId":1073872969,"Properties":[469775450,"Resumen",201340122,"2",134234082,"true",134233614,"true",469778129,"Resumen",335572020,"1",469777841,"Cambria",469777842,"Times New Roman",469777843,"MS Mincho",469777844,"Cambria",469769226,"Cambria,Times New Roman,MS Mincho",335551500,"4278190080",335557856,"4278190080",268442635,"19",335551547,"13322",335559740,"240",201341983,"0",335559739,"180",335551550,"6",335551620,"6",469778324,"Normal"]}">Introduction: The assessment of patients with pulmonary tuberculosis is useful to establish health intervention goals. The 6-minute walk test is key to observing the response of all of the body systems involved in the exercise. Objective: To describe the physiological response of some ventilatory and cardiovascular variables during the 6-minute walk test in patients with pulmonary tuberculosis sequelae and possible correlations between physiological variables and the covered distance. Materials and methods: Descriptive cross-sectional study on 21 patients diagnosed with sequelae caused by pulmonary tuberculosis, who attended a pulmonary rehabilitation program and performed a 6-minute walk test. Results: The mean age of patients was 49.33±18.82 years, mostly men, and the mean distance was 348.35±127833 m. There was a significant difference in heart rate, respiratory rate and oxygen saturation during the four analyzed moments, with a p value < 0.0001. There was a strong correlation for age, oxygen consumption (VO2), number of stops, dyspnea modified Medical Research Council (mMRC), functional capacity measured as metabolic equivalents (METS) and oxygen saturation (SpO2). Conclusion: Most male patients with pulmonary tuberculosis sequelae show statistically significant changes during the test.